Elderly and caregiver demand: proposal for a care need classification - Daniella Pires Nunes; Tábatta Renata Pereira de Brito; Ligiana Pires Corona; Tiago da Silva Alexandre; Yeda Aparecida de Oliveira Duarte (Revista Brasileira de Enfermagem)
ABSTRACT Objective: To propose a care need classification for elderly people by identifying their functional demands. Method: Cross-sectional study carried out in São Paulo, in 2006, with 1,413 elderly (≥ 60 years old), participants in the Health, Well-being and Aging study (SABE – Saúde, Bem Estar e Envelhecimento). For the care need classification, we used the Guttman Scaling method e the frequency of assistance required by the elderly. Results: The hierarchy of activities of daily living had good internal consistency (α = 0.92) and satisfactory coefficients of reproducibility (98%), scalability (84%) and minimum marginal reproducibility (87%). Care need was categorized into: no need (requires no caregiver), minimum need (requires caregiver sporadically), moderate need (requires caregiver intermittently) and maximum need (requires full-time caregiver). Conclusion: This classification will allow identifying elderly that need assistance in everyday activities and will orientante health professionals in the development of a line of care.